2017
DOI: 10.20884/1.sb.2017.4.4.609
|View full text |Cite
|
Sign up to set email alerts
|

Penambahan Ekstrak Kulit Buah Naga Ke Dalam Pengencer Tris Kuning Telur Untuk Meningkatkan Kualitas Semen Beku Kambing Peranakan Ettawa

Abstract: A B S T R A C TThe success of artificial insemination is determined by the quality of the frozen semen used. Free radicals and cold shock may reduce the quality of frozen semen. These can be prevented or reduced by the addition of antioxidants. Dragon fruit skin extract is rich in natural antioxidants. This study is aimed to analyze the effect of the addition of dragon fruit skin extract on quality (motility, viability, and abnormality) of frozen goat semen. The most effective concentration in frozen semen. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
2
0
6
Order By: Relevance
“…Individual motility of goat semen in this study is 45.8%. This semen is still can be used for further process because the previous study which using motility 43% showed that the post-thawing motility is 15-26% [19]. The post-thawing motility 20% still can be used for insemination [20].…”
Section: Results and Discussion The Quality Of Fresh Semenmentioning
confidence: 99%
“…Individual motility of goat semen in this study is 45.8%. This semen is still can be used for further process because the previous study which using motility 43% showed that the post-thawing motility is 15-26% [19]. The post-thawing motility 20% still can be used for insemination [20].…”
Section: Results and Discussion The Quality Of Fresh Semenmentioning
confidence: 99%
“…Rataan persentase motilitas spermatozoa hasil penelitian ini sebesar 43,30 ± 3,08% lebih tinggi dibandingkan dengan penelitian Siswandoko et al (2017) yaitu 41± 4,18%. Hal ini mungkin disebabkan oleh perbedaan level EKBN yang digunakan yang selanjutnya akan berkorelasi dengan konsentrasi antioksidan serta zat nutrisi yang terkandung di dalamnya.…”
Section: Pengaruh Perlakuan Terhadap Kualitas Spermatozoaunclassified
“…Kualitas spermatozoa dikatakan baik jika memiliki jumlah spermatozoa yang hidup tinggi dan spermatozoa mati <15% (Bintara, 2011). Rataan persentase viabilitas spermatozoa pada penelitian ini adalah 50,16 ± 2,71% lebih rendah daripada hasil penelitian Siswandoko et al, (2017) Abnormalitas merupakan kelainan bentuk yang dialami oleh spermatozoa. Bentuk spermatozoa yang normal terdiri dari kepala, leher bagian tengah (badan) dan ekor yang sesuai dengan bentuk morfologinya.…”
Section: Pengaruh Perlakuan Terhadap Kualitas Spermatozoaunclassified
See 1 more Smart Citation
“…Pemanfaatan pengencer berbasis bahan alami telah banyak diteliti, di antaranya penelitian pemanfaatan ekstrak kulit buah naga (Siswandoko et al, 2017) dan ekstrak bawang merah (Kurniawan et al, 2018) dan pada kambing peranakan etawa. Hasil penelitian Siswandoko et al (2017), menunjukkan bahwa pengencer tris kuning telur dengan suplementasi ekstrak kulit buah naga berpengaruh signifikan dalam meningkatkan kualitas semen beku kambing PE.…”
unclassified